THE EFFECT OF PRODUCT INNOVATION AND SERVICESCAPE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AT LAIN HATI COFFEE SHOP IN TERNATE - Nurul Syafa Gani; Ida Hidayanti; Ririn Damayanti (IAIN Surakarta, 2022)
This study aims to determine the effect of product innovation and servicescape on customer loyalty through customer satisfaction. This research was a quantitative research. The population in this study was the other coffee consumers in the city. The number of research samples was 140 respondents. The data analysis technique in this research used path modeling analysis using Smart Partial Least Square (PLS) version 3 as a statistical test tool. The results of this study indicate that: (1) Product innovation has no significant effect on customer loyalty; (2) Servicescape has a significant effect on customer loyalty; (3) Product innovation has a significant effect on customer satisfaction; (4) Servicescape has a significant effect on customer satisfaction; (5) Customer satisfaction has a significant effect on customer loyalty; (6) Product innovation has a significant effect on customer loyalty through customer satisfaction; (7) Servicescape has no significant effect on customer loyalty through customer satisfaction.